Tolerance to Proinsulin-1 Reduces Autoimmune Diabetes in NOD Mice - Jhala, Gaurang; Selck, Claudia; Chee, Jonathan; Kwong, Chun-Ting J.; Pappas, Evan G.; Thomas, Helen E.; Kay, Thomas W.H.; Krishnamurthy, Balasubramanian (Frontiers in Immunology, 2021)
T-cell responses to insulin and its precursor proinsulin are central to islet autoimmunity in humans and non-obese diabetic (NOD) mice that spontaneously develop autoimmune diabetes. Mice have two proinsulin genes proinsulin -1 and 2 that are differentially expressed, with predominant proinsulin-2 expression in the thymus and proinsulin-1 in islet beta-cells. In contrast to proinsulin-2, proinsulin-1 knockout NOD mice are protected from autoimmune diabetes. This indicates that proinsulin-1 epitopes in beta-cells maybe preferentially targeted by autoreactive T cells. To study the contribution of proinsulin-1 reactive T cells in autoimmune diabetes, we generated transgenic NOD mice with tetracycline-regulated expression of proinsulin-1 in antigen presenting cells (TIP-1 mice) with an aim to induce immune tolerance. TIP-1 mice displayed a significantly reduced incidence of spontaneous diabetes, which was associated with reduced severity of insulitis and insulin autoantibody development. Antigen experienced proinsulin specific T cells were significantly reduced in in TIP-1 mice indicating immune tolerance. Moreover, T cells from TIP-1 mice expressing proinsulin-1 transferred diabetes at a significantly reduced frequency. However, proinsulin-1 expression in APCs had minimal impact on the immune responses to the downstream antigen islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) and did not prevent diabetes in NOD 8.3 mice with a pre-existing repertoire of IGRP reactive T cells. Thus, boosting immune tolerance to proinsulin-1 partially prevents islet-autoimmunity. This study further extends the previously established role of proinsulin-1 epitopes in autoimmune diabetes in NOD mice.